ANALISIS FAKTOR PENENTU NIAT PENGGUNAAN E-COMMERCE DI KALANGAN GENERASI Z: STUDI PADA UBIQUITOUS CONNECTIVITY, INFORMATION TRANSPARENCY, DAN INFORMATION OVERLOAD - Halim, Joceline Eloysa; F.C.W. Sutrisno, Timotius; Andrina, Anak Agung Ayu Puty (FEB Universitas Sam Ratulangi Manado, 2024)
The growth of e-commerce in Indonesia has encouraged people to adopt online shopping. Shopee, as one of the global e-commerce platforms, has successfully dominated the Indonesian market. This study aims to examine the influence of Ubiquitous Connectivity, Information Transparency, and Information Overload on Usage Intention. The study employs Protection Motivation Theory (PMT) and Information Processing Theory (IPT). The method used is quantitative with a purposive sampling technique. Data were analyzed using SEMPLS through a structural equation model, with respondents from Generation Z in Surabaya. The results of this study reveal that Ubiquitous Connectivity, Information Transparency, and Information Overload significantly influence Usage Intention. These findings highlight the importance of Ubiquitous Connectivity, Information Transparency, Information Overload, and Usage Intention in e-commerce, particularly among Generation Z. This study is expected to help e-commerce platforms enhance their applications to provide better convenience for users.